Averting disaster science for peace in a perilous age the Erice International Seminars on Nuclear War and Planetary Emergencies, from 1981 to 2008 - Barletta, W. A. (William A.); Wegener, Henning (Science and culture series. Nuclear strategy and peace technology, 2010)
Reminiscences from participants in Erice International Seminars on Planetary Emergencies